New directions in education policy implementation : confronting complexity - Honig, Meredith I. [Mitarbeiter]; Coburn, Cynthia E. [Mitarbeiter]; Stein, Mary Kay [Mitarbeiter]; Spillane, James P. [Mitarbeiter]; Reiser, Brian J. [Mitarbeiter]; Gomez, Louis M. [Mitarbeiter]; Hill, Heather C. [Mitarbeiter]; Malen, Betty [Mitarbeiter]; Datnow, Amanda [Mitarbeiter]; Dumas, Michael J. [Mitarbeiter]; Anyon, Jean [Mitarbeiter]; Loeb, Susanna [Mitarbeiter]; et al. (State Univ. of New York Press, 2006)
"This book presents original work by a new generation of scholars contributing to education policy implementation research. The contributors define education policy implementation as the product of the interaction among particular policies, people, and places. Their analyses of previous generations of implementation research reveal that contemporary findings not only build directly on lessons learned from the past, but also seek to deepen past findings. These contemporary researchers also break from the past by seeking a more nuanced, contingent, and rigorous theory-based explication of how implementation unfolds. They argue that researchers and practitioners can help improve education policy implementation by not asking simply what works, but rather focusing their attention on what works, for whom, where, when, and why." (Verlag, BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; S 4.3 Steuerung; T 2.3 Handlungstheorien; Bildungspolitik; Bildungssteuerung; Aktionsforschung; Implementation